Pemanfaatan Biji Nangka dan Biji Kluwih Sebagai Pendukung Produk Pound Cake - Rizkyka, Yane; Riyanti, Anti (Manajemen dan Pariwisata, 2024)
Cake is favored by people from all walks of life, due to its dominant sweet flavor and soft texture. Efforts to develop pastry products can be made by modifying processed pastry products made from wheat flour. One of them is in making cakes with the substitution of jackfruit seed flour and kluwih seed flour. Assess and develop cake products by utilizing jackfruit seed flour and kluwih seed flour into quality cake products. To achieve these goals, a good research and development method is needed. This Product Research and Development method is the Analysis, Design, Develop or Production, Implementation or Delivery, and Evaluation model and organoleptic test by creating new innovations in the world of pastiseri. The author found 3 different recipe formulations in this study. The author applied with 100% wheat flour substitution, then 50% wheat flour substitution combined with 50% substitution of jackfruit seed flour and kluwih seeds, and with 100% substitution of jackfruit seed flour and kuluwih seeds. The composition of the cake making formula with supporting ingredients of jackfruit seed flour and kluwih seed flour as much as 50% of the ratio has changed which is acceptable to the general public. Modifications to butter cake whose main ingredient is 50% wheat flour and 50% jackfruit seed flour and kluwih seed flour are still acceptable and become new cake innovations in the world of pastiseri.